2003
DOI: 10.1002/per.483
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the multicultural personality questionnaire in the context of personnel selection

Abstract: The present data provide support for the reliability of the Multicultural Personality Questionnaire among a sample of job applicants (n ¼ 264). Factor analysis confirmed five factors: Cultural Empathy, Open-Mindedness, Social Initiative, Flexibility, and Emotional Stability. Moreover, the data largely support the construct validity of the MPQ. Correlations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 50 publications
(78 reference statements)
4
41
2
Order By: Relevance
“…Van der Zee and Van Oudenhoven's (2001) five-factor MPQ structure was supported in additional exploratory factor analyses (30.3% of variance accounted for; Van der Zee et al, 2003) and confirmatory factor analyses in both Dutch and Italian university students (Comparative Fit Indexes of .90 and .91; Leone, Lucidi, Ercolani, & Presaghi, 2003 Perugini, & Ercolani, 2005). In an integrative review of 15 studies incorporating the MPQ, Ponterotto (2008) found strong support for score construct and criterion validity.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Van der Zee and Van Oudenhoven's (2001) five-factor MPQ structure was supported in additional exploratory factor analyses (30.3% of variance accounted for; Van der Zee et al, 2003) and confirmatory factor analyses in both Dutch and Italian university students (Comparative Fit Indexes of .90 and .91; Leone, Lucidi, Ercolani, & Presaghi, 2003 Perugini, & Ercolani, 2005). In an integrative review of 15 studies incorporating the MPQ, Ponterotto (2008) found strong support for score construct and criterion validity.…”
Section: Methodsmentioning
confidence: 89%
“…Though both the Emotional Intelligence Scale (EIS; Schutte et al, 1998) and the Multicultural Personality Questionnaire (MPQ; Van der Zee & Van Oudenhoven, 2000 are considered appropriate measures for their constructs (Ciarrochi et al, 2001;Ciarrochi et al, 2002;Ponterotto, 2008;Van der Zee et al, 2003;Van Rooy & Viswesvaran, 2004;Van Rooy et al, 2005), there is still some questions about the best-fit factor structure for each measure (e.g., Keele & Bell, 2008;Petrides & Furnham, 2000;Ponterotto, 2008). Large sample national and international research incorporating confirmatory factor analysis is needed to more closely examine the construct validity of each measure, particularly Schutte and colleagues' (1998) EIS.…”
Section: Downloaded By [Kungliga Tekniska Hogskola] At 16:28 05 Octobmentioning
confidence: 98%
“…In MPQ studies, men scored higher than women on Emotional Stability (Ponterotto, Costa-Wofford, Brobst, Spelliscy, Scheinholtz, & Martinez, 2007;Van der Zee & Brinkman, 2004;Van der Zee & Van Oudenhoven, 2000), and women higher than men on Cultural Empathy (Van der Zee, Zaal, & Piestra, 2003).…”
Section: Control Variablesmentioning
confidence: 97%
“…Norman (1963) originally called this trait Culture and others have called it Intellect (Digman & Takemoto-Chock, 1981). Most of this research has suggested a positive relationship between Openness-to-Experience and intelligence (e.g., Bates & Shieles, 2003;Van der Zee, Zaal, & Piekstra, 2003). This positive relationship comes as little surprise as Openness-to-Experience is the personality trait considered to be most conceptually similar to intelligence (Barrick & Mount, 1991;Eysenck, 1992;McCrae & Costa, 1997).…”
mentioning
confidence: 91%